1999
DOI: 10.4269/ajtmh.1999.61.308
|View full text |Cite
|
Sign up to set email alerts
|

Early, intermediate, and late acute stages in Chagas' disease: a study combining anti-galactose IgG, specific serodiagnosis, and polymerase chain reaction analysis.

Abstract: Abstract. The acute phase of Chagas' disease was classified as early, intermediate, and late based on the levels of anti-Gal␣ 1,3 Gal IgG (Gal) and specific IgM (M) and IgG (G) anti-T. cruzi reactivity. While the early phase was MϩG-GalϪ, the intermediate phase was MϩG-Galϩ, MϩGϩGalϪ, or MϩGϩGalϩ, and the late phase was MGϩGalϩ. This sequence of stages was consistent with our previous studies on acute-phase proteins. Analysis by the polymerase chain reaction (PCR) of parasite DNA in 65 blood samples of childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 23 publications
(27 reference statements)
3
24
0
1
Order By: Relevance
“…The two others cases may be considered as false positive PCR, but a singular situation has been previously described in Bolivia where cases of positive xenodiagnosis with negative serology were reported (Brenière et al 1984). High sensitivity of PCR using kDNA primers has been demonstrated in different studies performed with Bolivian populations in endemic areas , Antas et al 1999. Seroprevalence increased regularly with the age of the patients as previously observed in a study of 140 individuals in a rural community of Cochabamba department (Pless et al 1992).…”
Section: Discussionmentioning
confidence: 70%
“…The two others cases may be considered as false positive PCR, but a singular situation has been previously described in Bolivia where cases of positive xenodiagnosis with negative serology were reported (Brenière et al 1984). High sensitivity of PCR using kDNA primers has been demonstrated in different studies performed with Bolivian populations in endemic areas , Antas et al 1999. Seroprevalence increased regularly with the age of the patients as previously observed in a study of 140 individuals in a rural community of Cochabamba department (Pless et al 1992).…”
Section: Discussionmentioning
confidence: 70%
“…In this sense, it is remarkable the presence of one asymptomatic 2 years old girl. This finding, added to the presence of very suggestive cases of acute Chagas in another 2 girls, and in an adult with fever and hepatomegaly, although not confirmed by parasitemia, but positive for IIF and PCR, that are considered strong evidence of acute Chagas disease by some authors (Añez et al 1999, Antas et al 1999, verifies the assumption that there is active transmission of AT and human Chagas disease in Colima. For this reason, acute Chagas disease should be considered in the differential diagnosis of persistent fever, especially in cases accompanied by systemic manifestations in areas where domiciliated triatominae are detected.…”
Section: Discussionmentioning
confidence: 78%
“…Although classic studies have suggested a suppressive response in the early phases of human T. cruzi infection [24,25], it is clear that the immune response mounted is efficient for controlling patent parasitemia. It has been suggested that B-cell activation leading to lytic antibody production is important in parasite elimination during the acute phase [26][27][28]. Although studies of endomyocardial biopsies from acute patients have shown the presence of CD4+ and CD8+ T cells in the inflammatory myocarditis [29], the function of these cells during the acute phase has not been determined.…”
Section: How the Early Encounter Of Trypanosoma Cruzi With Host Cellsmentioning
confidence: 99%